1995
DOI: 10.2135/cropsci1995.0011183x003500050022x
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Drought‐Induced Losses in Grain Yield: Sucrose Maintains Embryo Growth in Maize

Abstract: Large losses in yield can occur in maize (Zea mays L.) growing in water‐limited conditions (low Ψw), particularly during flowering and early embryo growth where grain number is decreased. However, embryo growth is maintained where otherwise none would occur if the stems are infused with photosynthate (sucrose) and other nutrients (amino acids, salts, vitamins, and hormones) during exposure to low Ψw. In the present investigation, we deleted or supplied various components of the complete infusion mediumto ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
110
2
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 0 publications
12
110
2
3
Order By: Relevance
“…Therefore, the present study was conducted to find out the possible involvement of potassium deficiency in maize kernel abortion and the impact of foliar-applied K in improving grain formation during pre-anthesis drought. Results showed that drought stress around pollination severely decreased the number of grains per cob in maize which coincides with a number of similar studies (Zinselmeier et al, 1995(Zinselmeier et al, , 1999Andersen et al, 2002;McLaughlin and Boyer, 2004). The decrease in grain number is generally associated with an accumulation of sugars in source leaves and a poor supply of sugars to developing kernels (Zinselmeier et al, 1995(Zinselmeier et al, , 1999Heutsch et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, the present study was conducted to find out the possible involvement of potassium deficiency in maize kernel abortion and the impact of foliar-applied K in improving grain formation during pre-anthesis drought. Results showed that drought stress around pollination severely decreased the number of grains per cob in maize which coincides with a number of similar studies (Zinselmeier et al, 1995(Zinselmeier et al, , 1999Andersen et al, 2002;McLaughlin and Boyer, 2004). The decrease in grain number is generally associated with an accumulation of sugars in source leaves and a poor supply of sugars to developing kernels (Zinselmeier et al, 1995(Zinselmeier et al, , 1999Heutsch et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Water stress during reproductive growth predominantly affects grain setting and therefore severely damages grain yields. In maize, water stresses around pollination aborts the developing kernels by affecting sugar metabolism and assimilate transport (Zinselmeier et al, 1995;McLaughlin and Boyer, 2004;Huetsch et al, 2015). A decrease in sucrose hydrolysis leads towards sucrose accumulation in source leaves which decreases the sink capacity to support the developing kernels (McLaughlin and Boyer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos trabalhos sugerem que as falhas reprodutivas em milho ocorrem porque o suprimento de assimilados em plantas deficientes em água não é suficiente para manter o crescimento de todos os novos zigotos formados (Boyle et al, 1991;Shussler & Westgate, 1991;Zinselmeier et al, 1995a). Outra causa pode ser a inibição do alongamento do estilete e o retardamento na emergência dos estigmas, que fazem com que estes fiquem menos expostos à polinização (Westgate & Boyer, 1985;Basseti & Westgate, 1993).…”
Section: Introductionunclassified
“…Outra causa pode ser a inibição do alongamento do estilete e o retardamento na emergência dos estigmas, que fazem com que estes fiquem menos expostos à polinização (Westgate & Boyer, 1985;Basseti & Westgate, 1993). Zinselmeier et al (1995b) observaram redução de 45 a 65% do número de grãos por espiga em plantas de milho submetidas a potenciais da água na folha entre -0,82 e -1,2 MPa, no período das 8 às 10h, durante a emergência dos estigmas e polinização.…”
Section: Introductionunclassified
“…Drought stress is a major environmental stress that has negative impacts on plant growth and development which limits plant performances and productivity causing the loss of about 50% of agricultural yields worldwide (Bray et al, 2000).It inhibits cell growth, cell expansion thereby affecting leaf extension, leaf area, chlorophyll content, growth rate, reproductive development and source-sink relationship (NeSmith and Ritchie, 1992;Hsiao and Xu, 2000;Pandey et al, 2000;Jaleel et al, 2009). Meiosis, anthesis, male and female reproductive stage are all extremely susceptible to drought stress thus leading to a significant yield penalty (Cattivelli et al, 2008;Zinselmeier et al, 1995).…”
Section: Introductionmentioning
confidence: 99%